Area Oversizing of Lithium Metal Electrodes in Solid‐State Batteries: Relevance for Overvoltage and thus Performance?. Issue 10 (28th April 2021) - Stolz, Lukas; Homann, Gerrit; Winter, Martin; Kasnatscheew, Johannes
Abstract: Invited for this month′s cover is the group of Dr. Johannes Kasnatscheew from the Research Center Jülich GmbH. The image shows how area oversizing of lithium can affect the overall power of batteries, in particular at lower temperature. The Full Paper itself is available at 10.1002/cssc.202100213 . Abstract : "A significant boost in specific energy and specific power…" This and more about the story behind the research that inspired the Cover image is presented in the Cover Profile. Read the full text of the corresponding research at 10.1002/cssc.202100213 . View the Front Cover here: 10.1002/cssc.202100779 .